A provably secure password-based anonymous authentication scheme for wireless body area networks. (January 2018) - Wei, Fushan; Vijayakumar, P.; Shen, Jian; Zhang, Ruijie; Li, Li
Highlights: Proposing the first password-based anonymous authentication scheme for WBANs. Enjoying formal security proof in the random oracle model. Achieving strong user anonymity. Efficient in terms of computation. Graphical abstract: Abstract: Wireless body area networks (WBANs) comprise many tiny sensor nodes which are planted in or around a patient's body. These sensor nodes can collect biomedical data of the patient and transmit these valuable data to a data sink or a personal digital assistant. Later, health care service providers can get access to these data through authorization. The biomedical data are usually personal and privacy. Consequently, data confidentiality and user privacy are primary concerns for WBANs. In order to achieve these goals, we propose an anonymous authentication scheme for WBANs based on low-entropy password and prove its security in the random oracle model. Our scheme enjoys strong anonymity in the sense that only the client knows his identity during the authentication phase of the scheme. Compared with other related proposals, our scheme is efficient in terms of computation. Moreover, the authentication of the client relies on human-rememberable password, which makes our scheme more suitable for applications in WBANs.